Real Work Lecture: Community Service in Making Simple Water Filters in Tulung Village, Gresik - Yauwan Tobing Lukiyono; Paramita Sari; Inayah Hikmawati; Muhammad Firmansyah; Alifia Az Zahra; Nasyah Nuraulia (Journal of Health Community Service, 2023)
Water is the source of life on earth. Clean water is a basic human need. The limited availability of water and the ever-increasing population has led to a drinking water crisis. The water emits an unpleasant odor and has a cloudy color, as experienced by the residents of Tulung village. This area is located in Kedamean District, Gresik Regency. This village is an area that does not yet have PDAM water supply. Most residents of Tulung Village still use the reservoir water for drinking, cooking, bathing and washing. To overcome these problems, one of the alternative solutions so that reservoir water can meet the physical, chemical and bacteriological requirements is to purify the water using the filtration method. Filtration method is the process of filtering water to remove suspended solids from water through a porous medium. Through the 2023 Real Work Program activities with the theme "Making Simple Water Filter in Tulung Village, Gresik" able to provide knowledge and understanding to the residents of Tulung Village as activity partners.